Literature Review: Pengaruh Minyak Zaitun dalam Mencegah Luka Tekan: Literature Review: The Influence of Olive Oil in Preventing Pressure Sores - Amzal Mortin Andas; Ashar Prima; Nisa Alifah; Fauziah H Wada (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Pressure ulcers are injuries due to prolonged pressure on the skin and tissues, leading to more serious conditions. This can cause necrosis in patients who have long bed rest. Efforts to prevent pressure ulcers should be carried out as early as possible since the patient is at risk of developing pressure ulcers. Olive oil contains saturated and unsaturated fatty acids, vitamin E, and oleic acid, which can protect the skin from damage. This literature review aims to determine the effect of olive oil in preventing pressure ulcers. The literature review uses searched google scholar, PubMed, and science direct in this scientific paper. The keywords used in the search were Pressure ulcers, olive oils, and prevention. The inclusion criteria were used in the article that is the subject of patients with pressure ulcers, manuscript full text, speak English and Indonesian, the article last over 10 years, according to research topics, and results found 4 articles from google scholar. A literature review of 4 articles showed that olive oil was effectively given at the age of 20-80 years with regular use 2 times a day for 7 days to help prevent pressure ulcers. The literature review results show that olive oil can prevent pressure ulcers.